2006
DOI: 10.1080/13102818.2006.10817303
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships between Salt Stress and Anthocyanin Content in Higher Plants

Abstract: The relationships between salt stress and anthocyanin content in the roots, hypocotyls and cotyledons of some higher plants (tomato and red cabbage) were investigated. Plants were exposed to various concentrations of NaCl at all of their developmental stages. The germinated seeds were selected and transferred to water culture chamber containing ¼ strength Hoagland's nutrient solution supplied with 0 (control) and 50, 100 mM NaCl. After 7 days the uniform seedlings were harvested for experimental analysis. Tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(66 citation statements)
references
References 28 publications
4
51
1
2
Order By: Relevance
“…These results suggest that anthocyanin is an important flavonoid as a modulator of salinity stress and plays an important role in the prevention of stress-induced oxidative damage in leaves of almost all rice varieties except for the salttolerant BC2F7#62-56. These results were supported by Eryılmaz 29 , reporting that there was a correlation in the increases of anthocyanins with salt stress in tomato and red cabbage seedlings.…”
Section: Effect Of Salinity On Anthocyanin Cyanidin-3-glucoside Contentsupporting
confidence: 78%
“…These results suggest that anthocyanin is an important flavonoid as a modulator of salinity stress and plays an important role in the prevention of stress-induced oxidative damage in leaves of almost all rice varieties except for the salttolerant BC2F7#62-56. These results were supported by Eryılmaz 29 , reporting that there was a correlation in the increases of anthocyanins with salt stress in tomato and red cabbage seedlings.…”
Section: Effect Of Salinity On Anthocyanin Cyanidin-3-glucoside Contentsupporting
confidence: 78%
“…Chlorophyll and carotenoid levels are considered to be indicators of salt stress in plants. Because the levels of the main photosynthetic pigments, chlorophyll a, chlorophyll b, and carotenoids, are significantly affected by salt stress, these are used as parameters to select tolerant and sensitive cultivars of crop plants (Eryilmaz, 2007;Rahdari et al, 2012). Besides, the level of MDA is a measure of membrane lipid peroxidation damage caused by abiotic stresses and it is an important indication of oxidative damage under conditions of salt stress (Liang et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the reduction in photosynthetic pigments (chlorophyll a, chlorophyll b, and total carotenoids) due to salinity effect which attributed to the disturbance of ions absorption involved in chloroplast formation and protein synthesis and/or plastid breakdown (Abd El-Wahab, 2006). However, it was observed that the degradation of chlorophyll pigments was increased as a result of exposure to NaCl (Eryilmaz, 2006). Table (3) showed that medium with 5 mg/l Phenylalanine and free from sodium chloride gave the highest values of total chlorophyll content (390.79) in shootlets, while medium with 10 mg/l Phenylalanine and free from sodium chloride gave the lowest value of total chlorophyll content (10.83) in callus.…”
Section: Resultsmentioning
confidence: 93%